PENGARUH PENGUASAAN BAHASA FIGURATIF DAN MINAT BACA TERHADAP KEMAMPUAN MERESEPSI CERITA PENDEK - Winda Sofidiniawati; Sumaryoto Sumaryoto; Hasbullah Hasbullah (Universitas Indraprasta PGRI, 2022)
AbstractThis study aims to find 1) The effects of mastery of figurative language and reading interest together on the ability to perceive short stories in private junior high school students in Bekasi Regency. 2) The effect of mastery of figurative language on the ability to perceive short stories in private junior high school students in Bekasi Regency. 3) The effect of reading interest on the ability to perceive short stories in private junior high school students in Bekasi Regency. The sample used in this study was 75 students with simple random sampling technique. The statistical model used is multiple linear regression. The results of the study concluded: 1) There are a significant effect of mastery of figurative language and reading interest together on the ability to perceive short stories in private junior high school students in Bekasi Regency.It is proved by sig. 0.000 < 0.05 and Fobserved= 88.739; 2) There is a significant effect of mastery of figurative language on the ability to perceive short stories in private junior high school students in Bekasi Regency. It is proved by Sig. = 0,000 <0.05 and tobserved= 6,184; 3) There is a significant effect of reading interest on the ability to perceive short stories in private junior high school students in Bekasi Regency. It is proved by Sig. = 0,021 <0.05 and tobserved= 2,367. Keywords:Mastery of Figurative Language, Interest in Reading, Ability to Perceive Short Stories